The dove in the consulting room : hysteria and the anima in Bollas and Jung - Mogenson, Greg, 1959- (Brunner-Routledge, 2003)
This provocative and original book critically engages with psychoanalysis and in particular the phenomenon of the return of hysteria to analysis, from a Jungian perspective.